The Intellectual Content of Print Designs among Students of Fine Arts Institutes and Its Relationship with Executive Attention - اخلاص عبد القادر طاهر حسين; نورا عبـد الله علي (Basrah Arts Journal, 2026)
This research investigated the relationship between the intellectual content (thematic and conceptual depth) of print designs created by Fine Arts students and their executive attention capabilities. Employing a descriptive correlational method, the study was conducted with a sample of 19 third-year students from a population of 79. Researchers developed and validated two instruments: an executive attention test and an analytical skill observation form to assess intellectual content in designs. Key findings identified and measured two components of executive attention: 1.Focused Attention: The preparatory ability to orient the sensory system toward specific stimuli. 2.Shifting Attention: The flexible ability to transition and respond between different tasks or stimuli. 3.Statistical analysis revealed a significant positive correlation. The skill performance in generating intellectual content (the independent variable) accounted for 10.44% of the variance in executive attention scores (the dependent variable). Principal conclusions indicate that: Richer intellectual content in student print designs correlates with higher levels of executive attention. This intellectual content streamlines and facilitates the executive attention required during the printmaking skill performance. Educational content enriched with topic-specific activities effectively creates a focal point to engage and direct executive attention.